2023
DOI: 10.1186/s13054-023-04548-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of AI-assisted lung ultrasound in a resource-limited intensive care unit

Abstract: Background Interpreting point-of-care lung ultrasound (LUS) images from intensive care unit (ICU) patients can be challenging, especially in low- and middle- income countries (LMICs) where there is limited training available. Despite recent advances in the use of Artificial Intelligence (AI) to automate many ultrasound imaging analysis tasks, no AI-enabled LUS solutions have been proven to be clinically useful in ICUs, and specifically in LMICs. Therefore, we developed an AI solution that assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…An interesting emerging field of study could be the introduction of new Artificial Intelligence (A.I.) techniques that can help in daily work and increase diagnostic performance, especially in “new user” radiologists [ 36 ]. This concept could be useful especially in medical centers in low- to middle-income countries where training resources are few; applying A.I.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting emerging field of study could be the introduction of new Artificial Intelligence (A.I.) techniques that can help in daily work and increase diagnostic performance, especially in “new user” radiologists [ 36 ]. This concept could be useful especially in medical centers in low- to middle-income countries where training resources are few; applying A.I.…”
Section: Discussionmentioning
confidence: 99%
“…The use of automation and computer-assisted algorithms could reduce inter-operator variability by aligning different settings and by standardizing the quantification of lung pathology through computerized image analysis. Its potential implementation in lung ultrasound may be a valuable future resource capable of overcoming many limitations and improving patient care [ 17 ]. The VLUP systematic, quick and well-defined approach could be helpful in further studies regarding a computer analysis of lung damage through artificial intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Data showed that when physicians, even if beginners, were supported by the AI tool, their performance improved, exceeding the level of advanced users. Of course, the support of AI does not yield a significant enhancement for an expert ultrasonographer [38]. Automatic detection of abnormalities and pathological findings in LUS has been proposed [39], with good concordance between expert observers and automatic detection in a point-of-care setting [40,41].…”
Section: Discussionmentioning
confidence: 99%